2006
DOI: 10.1038/sj.bjc.6603232
|View full text |Cite
|
Sign up to set email alerts
|

Large needle aspiration biopsy and galectin-3 determination in selected thyroid nodules with indeterminate FNA-cytology

Abstract: Thyroid fine-needle aspiration biopsy (FNA)-cytology is widely used for the preoperative characterisation of thyroid nodules but this task is difficult for follicular lesions, which often remain undefined. We propose a strategy for improving the preoperative characterisation of selected follicular thyroid proliferations, which is based on large needle aspiration biopsy (LNAB) and galectin-3 expression analysis. Eighty-five thyroid specimens were obtained by LNAB (20-gauge needles) from thyroid nodules with ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 49 publications
5
38
0
Order By: Relevance
“…Therefore, Gal-3 protein might be an additional and valuable molecular tool not only to augment the diagnosis of malignant intra-prostatic disease but to also determine the biological activity with regard to the intra-cellular localization of the protein [5]. The observation that already benign glands in the neighborhood of the primary solid tumors as well as PIN lesions tissues exhibit a staining pattern that is substantially different from that in prostate specimens obtained from patients with benign prostatic disease might help to differentiate more precisely between benign and malignant biopsies as supposed for small needle biopsies from thyroid cancer [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Gal-3 protein might be an additional and valuable molecular tool not only to augment the diagnosis of malignant intra-prostatic disease but to also determine the biological activity with regard to the intra-cellular localization of the protein [5]. The observation that already benign glands in the neighborhood of the primary solid tumors as well as PIN lesions tissues exhibit a staining pattern that is substantially different from that in prostate specimens obtained from patients with benign prostatic disease might help to differentiate more precisely between benign and malignant biopsies as supposed for small needle biopsies from thyroid cancer [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Although immunocytochemical evaluation of some tumorassociated antigens, such as galectin-3 (7)(8)(9)(10)(11)(12)(13)(14), cell surface mesothelial antigen HBME-1 (8,(14)(15)(16)(17), and cytokeratin-19 (8,16,17), was recently successfully introduced for the thyroid to improve preoperative cytologic diagnosis, the issue of follicular neoplasm remains incompletely solved and these lesions still need surgical procedures for a definitive diagnosis.…”
mentioning
confidence: 99%
“…Previous studies demonstrated that optimal staining with galectin-3, broadly reported as thyroid biomarker, requires formalin-fixed and paraffin-embedded preparations, biotin-free detection systems and application of specific monoclonal antibodies. Additionally, the conventional thyroid smears were reported to be inadequate for galectin-3 purposes [29], but its diagnostic properties are excellent on large-needle aspiration biopsy (LNAB) derived substrates [44]. Also the other markers including human mesothelial antigen (HBME-1), cytokeratin 19 (CK19), thyroid peroxidase (TPO) and keratan-sulphate (KS) or proteins related with energy metabolism such as alpha enolase (ENO1), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), pyruvate kinase isoenzymes M1/M2 (PKM1/ M2) and transketolase (TKT) employed to surgical thyroid or FNAB samples were reported to possess the diagnostic potential [45,22].…”
Section: Discussionmentioning
confidence: 99%